Effect of polyethylene cross-linking on properties of foams - Głuszewski Wojciech (Nukleonika, 2018)
The process of cross-linking of polyethylene using gamma radiation (γ) and electron beam (EB) was tested from the point of view of density of foam. Particular attention was paid to the postradiation oxidation effect of the polymers. The study used two types of radiation sources of varying dose rates: gamma radiation (4 kGy/h) and EB (14 000 kGy/h). Radiolysis studies of the polymers used the radiation yield of hydrogen evolved (GH2, approximately proportional to the number of radicals) and radiation yield of oxygen absorbed by the polymer (GO2). Oxidation of polymer due to radiation was also evaluated using diffuse reflectance spectroscopy.